Seismic displacement prediction methods, procedure, comparison and application - Rojas Gomez, Luis Felipe (2023)
The methodology in the seismic design of slopes has evolved with technological advancement and the development of geotechnical engineering. Since methods with great limitations such as pseudo-static analysis to rigorous methods that require a lot of information for a better understanding of the behavior of the soil such as the dynamic analysis.  This article develops the procedure, comparison, and application of methods for estimating seismic displacements, which are the Newmark (1965), Sarma (1975), Makdisi & Seed (1978) and Bray, Macedo & Travasarou (2018). Each of these methods considering the criteria of each one to obtain permanent displacements, such as yield acceleration, degraded period, spectral acceleration, magnitude, etc.  As an applicative case, a rockfill dam and core central 50 m high placed in sandstone strata and moraine deposits interspersed with shale intrusions is shown, as seismic scenarios the Lima 1974 earthquake, the Attic 2001 earthquake and the earthquake were used. of Pisco 2007, considering both NS and EW directions. Likewise, the response spectrum on the base of the failure surface, resulting from a nonlinear seismic response analysis from 3 columns in the dam, is considered as information. The methods of Newmark (1965), Sarma (1975), Makdisi & Seed (1978), and Bray, Macedo & Travasarou (2018) were applied, obtaining deformation results between 1 to 30 cm that according to their order of magnitude represent a stable condition for the dam.